The Third Hand of Neurosurgeons – a novel intraoperative malleable adjustable continuous suction tube - Zhang, Jibo; Nie, Pan; Wei, Zixuan; Xu, Chengshi; Li, Xiang; Chen, Jincao (Frontiers in Neurology, 2024)
Objective We designed a novel intraoperative malleable adjustable continuous suction tube to obtain clear surgical fields, reduce intracranial pressure, and lower the temperature of the surgical area. Methods This device consists of six parts: continuous suction tube head and cotton patty, suction tube, fixed wire position, fixed clip, spiral plastic pressure regulating valve, and tail. It can continuously extract blood, cerebrospinal fluid, and rinsing solution from surgical fields, with minimal contact and trauma to tissues, nerves, and blood vessels, while also having a negligible impact on the surgeon’s focus and procedure. Result The excellent and safe performance (simple, malleable, adjustable, space-saving, inexpensive, safe, and effective) of this device in clearing the operating field has been proven in more than 2000 neurosurgical operative procedures. We encountered no complications associated with this device, such as cerebral hematoma, postoperative low intracranial pressure, or vascular and nerve injuries. Conclusion The newly innovated intraoperative malleable adjustable continuous suction tube is effective and safe for microneurosurgery.